Inventorying Biodiversity of Anisakid Nematodes from the Austral Region: A Hotspot of Genetic Diversity? - Mattiucci, Simonetta; Paoletti, Michela; Cipriani, Paolo; Webb, Stephen C.; Timi, Juan Tomas; Nascetti, Giuseppe
Inventorying of anisakid nematode biodiversity is the discovering, surveying, quantifying and mapping of species, populations and their genetic diversity and variability. This aim, however, is compromised if discrimination of anisakid taxa relies solely on morphological features. Therefore, the accurate detection and delimitation of cryptic anisakid species requires molecular-based assessments. This, in turn, permits elucidation of patterns and process in their evolution and ecology, including biogeography, host-parasite association and co-evolution. In addition, a true picture of anisakids and their genetic diversity facilitates understanding of their temporal and spatial distribution also related to their hosts demographic changes and marine ecosystem food webs. This review represents an inventorying of the biodiversity, at species and gene level, of those anisakid species so far discovered belonging to the genera Anisakis, Pseudoterranova and Contracaecum, from the Austral Region, including: (1) taxa recognized as “biological species” based on the application of different molecular genetic markers; (2) current molecular/genetic approaches to identify them at any life-history stage; (3) ecological data relating to the geographical distribution, definitive host-association and host-preferences; (4) estimates of genetic variability values inferred from nuclear and mitochondrial genes, as a possible indicator of the integrity of marine food webs; (5) data so far known concerning the possible zoonotic role of those anisakid species to humans. Fil: Mattiucci, Simonetta. Università degli studi di Roma "La Sapienza"; Italia Fil: Paoletti, Michela. Universita Di Tuscia; Italia Fil: Cipriani, Paolo. Università degli studi di Roma "La Sapienza"; Italia. Universita Di Tuscia; Italia Fil: Webb, Stephen C. Cawthron Institute; Nueva Zelanda Fil: Timi, Juan Tomas. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y ...